Experience of nursing academic in the realistic simulation scenario about the evolution of diabetic neuropathy in old people (Research, Society and Development, 2020)
Objective: To describe the experience of nursing students in addressing the theme of Peripheral Diabetic Neuropathy in the elderly.Methodology: The study is an experience report carried out through a teaching methodology known as realistic simulation, with a class from the first semester of the Nursing course at the Federal University of Pará, which presented the role of the nurse in the evaluation of diabetic foot due to peripheral diabetic neuropathy.Results: Through simulation, it is possible to identify the relevance of this methodology, being a way to expose academics in a close reality which they will experience; Besides that, it was possible to obtain a positive opinion on the part of the students, who answered satisfactorily the questions exposed during the interactive action with the class. Conclusion: The experience allowed us to observe the applicability of this methodology for nursing teaching in the context of learning, nursing consultation as a tool for reflecting on clinical cases in the classroom.